2011
DOI: 10.1002/tox.20679
|View full text |Cite
|
Sign up to set email alerts
|

In utero and lactational exposure to PCB 118 and PCB 153 alter ovarian follicular dynamics and GnRH‐induced luteinizing hormone secretion in female lambs

Abstract: The effects of in utero and lactational exposure to two structurally different polychlorinated biphenyl (PCB) congeners on follicular dynamics and the pituitary-gonadal axis in female lambs were investigated. Pregnant ewes received corn oil, PCB 118, or PCB 153, and offspring was maintained until 60 days postpartum. Ovarian follicles were quantified using stereology. Plasma luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were measured using radioimmunoassay before and after administration of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
2
12
0
3
Order By: Relevance
“…Significant differences are shown by * p < .05. several genes encoding enzymes and receptors related to steroid hormone synthesis was also affected and mostly downregulated in fetuses with high PCB tissue levels. Kraugerud et al (2012) showed that F1 female lambs exhibited altered follicular dynamics and modulated responsiveness of the pituitary gland to gonadotropin releasing hormone (GnRH) after in utero and additional lactational exposure. Further, intrauterine exposure altered the sexually dimorphic behavior of offspring and altered bone density .…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences are shown by * p < .05. several genes encoding enzymes and receptors related to steroid hormone synthesis was also affected and mostly downregulated in fetuses with high PCB tissue levels. Kraugerud et al (2012) showed that F1 female lambs exhibited altered follicular dynamics and modulated responsiveness of the pituitary gland to gonadotropin releasing hormone (GnRH) after in utero and additional lactational exposure. Further, intrauterine exposure altered the sexually dimorphic behavior of offspring and altered bone density .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the suppressive actions of BPA on LH pulses depend on the dose, and high doses were required to replicate the actions of exogenous oestradiol (Collet et al 2010). Conversely, GnRH-stimulated LH release was higher in prepubertal female lambs exposed to PCB 118 (but not PCB 153) during gestation, indicative of selective PCB modulation of the responsiveness of the pituitary gland to hypothalamic stimulation (Kraugerud et al 2012). Both PCBs altered follicular dynamics in these lambs (see below) and may reflect an indirect effect on gonadotrophin release or a direct effect on the ovary.…”
Section: Effects Of Edcs On Pituitary Gonadotrophinsmentioning
confidence: 99%
“…Similarly, exposure to PCB 118 and PCB 153 throughout gestation altered follicular dynamics in prepubertal animals 60 days after birth. PCB 153 increased the number of primary follicles, whereas PCB 118 increased the sum of secondary, early antral and antral follicles (Kraugerud et al 2012). Although the long-term consequences of such enhanced development are unknown, Kraugerud et al (2012) suggest that increased recruitment from the primordial follicle pool could lead to premature ovarian failure.…”
Section: Effects Of Edcs On Ovarian and Uterine Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed also the adverse effect of PCBs on the most important hypothalamic factor controlling the synthesis and secretion of LHthe gonadotropin-releasing hormone (GnRH). Pituitary sensitivity to GnRH stimulation is known to be modulated by estrogens, so exposure to different PCBs, which exert estrogenic and/or anti-estrogenic activities, may change pituitary sensitivity to GnRH, resulting in disruption of GnRH-stimulated LH secretion , Desotelle et al 2005, Kraugerud et al 2012a.…”
Section: Discussionmentioning
confidence: 99%